Workplace health promotion to facilitate physical activity among office workers in Sweden - Halling Ullberg, Oskar; Toivanen, Susanna; Tillander, Annika; Bälter, Katarina (Frontiers in Public Health, 2023)
Office workers spend most of their working time being sedentary, contributing to a sedentary lifestyle that increases the risk of developing disease and disability. A gradual decline in cardiorespiratory fitness among adults, along with increased rate of non-communicable diseases across developed countries, makes the workplace an important opportunity for promoting healthy behaviors. This study aimed to investigate: how office companies in Sweden organize and provide workplace health promotion services related to physical activity; the companies' vision for providing workplace health promotion; and potential facilitators and barriers. Nine informants from eight companies participated in the study, and both qualitative and quantitative data were collected by semi-structured interviews. Informants were selected through purposive sampling in collaboration with eight companies in the office market, including companies that own and develop office buildings, shared workspaces, interior design, sustainable solutions, or consult on issues related to the office sector. The framework method was used to analyze the data in a flexible and systematic way. The results showed that workplace health promotion is implemented to maintain employee health, productivity, and employee branding. Also, a significant number of financial resources, organizational support and office space are devoted to workplace health promotion. Convenience and easy access to storage and fitness facilities are key facilitators. In conclusion, this study highlights the importance of employees' engagement in developing and improving workplace health promotion and addressing work-life balance constraints that hinder a healthy lifestyle. Removing barriers on an organizational level may improve the usage of workplace health promotion related to physical activity among office employees.